Performance Analysis of Air Gap Membrane Distillation Process Enhanced with Air Injection for Water Desalination - Jonathan Ibarra-Bahena; Ulises Dehesa-Carrasco; Rogelio Servando Villalobos-Hernández; Sofía Garrido-Hoyos; Wilfrido Rivera (Membranes)
Water scarcity is a global issue, and desalination is an alternative to providing fresh water. Renewable energies could be used in thermal desalination to produce freshwater from high saline concentration solutions. In this paper, the experimental performance of an air-injection-Air Gap Membrane Distillation (AGMD) module is presented. The effect of the operation parameters (saline solution temperature, air flow, and salt concentration) on the distilled water rate was evaluated. The air injection enhanced the distilled water rate by 22% at the highest air flow and a solution flow rate of 80 °C, compared to the conventional condition (without air injection) at a salt concentration of 100,000 ppm. Under the same operating conditions, the increase was 17% at a salt concentration of 70,000 ppm. The maximum distilled water rate was 14.10 L/m2·h at 80 °C and an airflow of 1.5 L/min with the highest salt concentration, while it was also 14.10 L/m2·h at the lower salt concentration was 14.10 L/m2·h. The distilled water quality also improved as the air flow increased, since a conductivity reduction of 66% was observed. With the described mathematical model, 94% of the calculated values fell within ±10% of the experimental data for both salt concentration conditions.